Backstory 5 : Interviews with Screenwriters of the 1990s. - McGilligan, Patrick (University of California Press, 2009)
Patrick McGilligan continues his celebrated interviews with exceptional screenwriters in Backstory 5, focusing on the 1990s. The thirteen featured writers-Albert Brooks, Jean-Claude Carrière, Nora Ephron, Ronald Harwood, John Hughes, David Koepp, Richard LaGravenese, Barry Levinson, Eric Roth, John Sayles, Tom Stoppard, Barbara Turner, and Rudy Wurlitzer-are not confined to the 1990s, but their engrossing, detailed, and richly personal stories create, in McGilligan's words, "a snapshot of a profession in motion." Emphasizing the craft of writing and the process of collaboration, this ne.
Keywords: Screenwriters -- California -- Los Angeles -- Interviews.; Scénaristes -- Californie -- Los Angeles -- Entretiens.; DRAMA -- American.; PERFORMING ARTS -- Film & Video -- General.; Screenwriters; California -- Los Angeles; 1990s.; adaptations.; albert brooks.; backstory.; barbara turner.; barry levinson.; behind the scenes.; biographical.; career.; collaborative projects.; contemporary.; david koepp.; eric roth.; fictional works.; jean claude carriere.; john hughes.; john sayles.; movie writers.; nonfiction.; nora ephron.; personal interviews.; pop culture.; popular movies.; popular television.; richard lagravenese.; ronald harwood.; rudy wurlitzer.; screenwriters.; stage plays.; television writers.; tom stoppard.; writing.; Interviews